Republic of Azerbaijan : 2016 Article IV Consultation-Press Release; Staff Report; and Informational Annex. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that the economic performance in Azerbaijan has been impaired by a number of negative shocks. Lower oil prices, weak regional growth, currency devaluations in its main trading partners, and a contraction in hydrocarbon production rapidly erased the large current account surplus the country enjoyed during the oil boom years. Near-term economic prospects remain weak. Under current policies, growth is expected to contract in 2016 and remain sluggish in the next few years, while inflation is expected to gradually decrease. The current account balance should improve as the devaluations work to limit imports and support nontraditional exports.